Flipped learning in action: Seven cases from Singapore’s Polytechnics (Journal of Applied Learning and Teaching, 2025)
Flipped learning reverses traditional direct instruction by having students complete homework before in-person classes. When supported by technology and data, flipped learning becomes a variant of blended learning, where blended learning refers to the integration of online and in-person learning experiences.This paper highlights the sector-wide shift to flipped learning in Singapore’s Polytechnics. The intent of the shift is to provide opportunities to improve self-directed learning, a critical skill set for the workforce. The authors consider seven presentations of practitioners’ early studies of flipped learning in action, all of which were delivered at the e-Learning Forum Asia 2023 conference.Key themes and takeaways from the seven presentations are considered, including the use of data and learning analytics to improve tailored support for self-directed learning, the value of learning-design models, examples of designing for social interaction during online asynchronous learning, to improve students’ confidence in learning and operational challenges such as the need for more time to implement quality flipped learning.The authors conclude with lessons for fellow practitioners to improve the designs of their own flipped learning efforts.